A Brief Review of Inpatient Palliative Rehabilitation - Bhavesh Patel; Vishwa Raj; Charles Mitchell; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2023)
Cancer patients face many challenges that can have a significant impact on their quality of life (QOL). When patients experience multiple functional impairments due to disease or treatment, their QOL and the efficient use of healthcare resources can be compromised. This is particularly true for patients who are nearing the end of their lives, as the physical and emotional burden of cancer can have a profound effect on both the individual and their caregivers. One approach to improving QOL in these patients is through palliative rehabilitation. Despite being an underutilized and understudied resource, palliative rehabilitation has shown promise in helping patients with advanced cancer retain their dignity and sense of control. By maximizing functional independence and reducing symptom burdens, palliative rehabilitation can provide a vital source of support for patients and their caregivers during this challenging time. Inpatient rehabilitation is one way that palliative rehabilitation can be applied in a healthcare setting. While further research is needed to fully understand the benefits of this approach, it is clear that palliative rehabilitation has the potential to play a key role in helping patients and their caregivers navigate the challenges of cancer treatment and end-of-life care. This approach is specific to the USA context but can be applied in other settings where cancer patients require such care. Keywords: Neoplasms / rehabilitation, Quality of life, Recovery of function, Survivors, Patient Care planning, Palliative.